2016
DOI: 10.1016/j.physrep.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity projections for dark matter searches with the Fermi large area telescope

Abstract: The nature of dark matter is a longstanding enigma of physics; it may consist of particles beyond the Standard Model that are still elusive to experiments. Among indirect search techniques, which look for stable products from the annihilation or decay of dark matter particles, or from axions coupling to highenergy photons, observations of the γ-ray sky have come to prominence over the last few years, because of the excellent sensitivity of the Large Area Telescope (LAT) on the Fermi Gamma-ray Space Telescope m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
174
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(181 citation statements)
references
References 347 publications
(593 reference statements)
5
174
0
2
Order By: Relevance
“…Projection studies include: CTA 5h [11] for photon-lines from GC (see refs. [41,42] for similar results), CTA 500h [43,44] for photon-continuum from GC, and Fermi-LAT 15 years for photon-continuum from 16 DG [45] (see ref. [46] for CTA projections).…”
Section: Annihilations At Gc and Dgmentioning
confidence: 60%
“…Projection studies include: CTA 5h [11] for photon-lines from GC (see refs. [41,42] for similar results), CTA 500h [43,44] for photon-continuum from GC, and Fermi-LAT 15 years for photon-continuum from 16 DG [45] (see ref. [46] for CTA projections).…”
Section: Annihilations At Gc and Dgmentioning
confidence: 60%
“…However, using the parameters in the allowed regions shown in Sec. 5, we have found that the pair annihilation cross section is much smaller than the current upper bounds obtained from, for example, the Fermi-LAT experiments [111]. 8 There is another process for the RHN DM to scatter off with nuclei via Z ′ -boson exchange.…”
Section: Direct Detection Of Rhn Dmmentioning
confidence: 75%
“…[38,39,41,[53][54][55] for the 95% (lighter) and 68% (darker) containment limits of the expected exclusion bound. As we can see, for their improved energy resolution, these experiments can probe a vast majority of the considered parameter space, covering in particular almost the totality of the region where the CoyDM model reproduces the GC photon excess.…”
Section: Gc Excessmentioning
confidence: 98%
“…We also consider the impact of the DAMPE [38,39,41], HERD [42] and GAMMA-400 [43] next generation experiments by estimating their reach from refs. [38,39,41,[53][54][55].…”
Section: Gc Excessmentioning
confidence: 99%